The Peroxisomal Targeting Signal 3 (PTS3) of the Budding Yeast Acyl-CoA Oxidase Is a Signal Patch - Kempiński, Błażej; Chełstowska, Anna; Poznański, Jarosław; Król, Kamil; Rymer, Łukasz; Frydzińska, Zuzanna; Girzalsky, Wolfgang; Skoneczna, Adrianna; Erdmann, Ralf; Skoneczny, Marek (Frontiers in Cell and Developmental Biology, 2020)
The specificity of import of peroxisomal matrix proteins is dependent on the targeting signals encoded within their amino acid sequences. Two known import signals, peroxisomal targeting signal 1 (PTS1), positioned at the C-termini and PTS2 located close to N-termini of these proteins are recognized by the Pex5p and Pex7p receptors, respectively. However, in several yeast species, including Saccharomyces cerevisiae, proteins exist that are efficiently imported into peroxisomes despite having neither PTS1 nor PTS2 and for which no other import signal has been determined. An example of such a protein is S. cerevisiae acyl-CoA oxidase (AOx) encoded by the POX1 gene. While it is known that its import is driven by its interaction with the N-terminal segment of Pex5p, which is separate from its C-terminal PTS1-recognizing tetratricopeptide domain, to date, no AOx polypeptide region has been implicated as critical for this interaction, and thus would constitute the long-sought PTS3 signal. Using random mutagenesis combined with a two-hybrid screen, we identified single amino acid residues within the AOx polypeptide that are crucial for this interaction and for the peroxisomal import of this protein. Interestingly, while scattered throughout the primary sequence, these amino acids come close to each other within two domains of the folded AOx molecule model. Although it is premature to call one or both of these regions the PTS3 signal, our data indicate that the signal guiding AOx into peroxisomal matrix not a linear sequence but a signal patch.